Modelling of laser ablation and reactive oxygen plasmas for pulsed laser deposition of zinc oxide - Rajendiran, S.; Rossall, A.K.; Gibson, A.; Wagenaars, E. (Surface and Coatings Technology, 2014)
Pulsed laser deposition (PLD) in a low-pressure oxygen atmosphere is commonly used for the production of high-quality, stoichiometric zinc oxide thin ﬁlms. An alternative approach that has the potential beneﬁt of increased process control is plasma-enhanced PLD, i.e. the use of a low-temperature oxygen plasma instead of a neutral gas. So far, the development of PE-PLD, and PLD in general, has been hampered by a lack of detailed understanding of the underpinning physics and chemistry. In this paper, we present modelling investigations aimed at further developing such understanding. Two-dimensional modelling of an inductively-coupled radiofrequency oxygen plasma showed that densities of 1014–1015 cm−3 of reactive oxygen species O and O2* can be produced for operating pressures between 3 and 100 Pa. Together with the absolute densities of species, also the ratio between different reactive species, e.g. O and O2*, can be controlled by changing the operating pressure. Both can be used to ﬁnd the optimum conditions for stoichiometric zinc oxide thin ﬁlm deposition. Additionally, we investigated laser ablation of zinc using a different two-dimensional hydrodynamic code (POLLUX). This showed that the amount of material that is ablated increases from 2.9 to 4.7 μg per pulse for laser ﬂuences from 2 to 10 J/cm2. However, the increased laser ﬂuence also results in an increased average ionisation of the plasma plume, from 3.4 to 5.6 over the same ﬂuence range, which is likely to inﬂuence the chemistry near the deposition substrate and consequently the ﬁlm quality.